Detection of human papillomavirus type 16 DNA and of antibodies to human papillomavirus type 16 proteins in children - Mund, Klaus; Han, C.; Daum, Roland; Helfrich, Stefan; Müller, M.; Fisher, S.G.; Schiller, J.T.; Gissmann, Lutz (Intervirology, 1997)
We have measured markers of human papillomavirus type 16 (HPV 16) infection in children (1-10 years of age) who were hospitalized for reasons unrelated to papillomavirus infection. Genital and buccal swabs obtained from 79 children were tested for the presence of HPV 16 DNA by PCR. Low-level positivity was found in 34 donors, twice as often in oral than in genital swabs. There was no sex-specific difference, but there was a trend towards a higher positivity rate with young age. Serum antibodies (IgG) were measured by ELISA based on peptides derived from the HPV 16 early proteins E4 (one peptide), E6 (two peptides) or E7 (two peptides) in 75 children and by ELISA based on virus-like particles in 66 children. Low-positivity rates were found for E6 (5.1%), E7 (2.5%) or capsid proteins (1.5%), but 20.3% of the sera reacted with the E4-specific peptide. There was no correlation between sero-positivity and the detection of HPV 16 DNA. In those instances where HPV DNA positivity in young children represents true infection and not environmental contamination, we speculate that this infection is accompanied by low-level virus replication that does not induce a measurable antibody response. Reactivity to the E4 protein is likely due to cross-reacting antibodies directed either against E4 proteins of other HPV types or against unrelated antigens.